ĐÁNH GIÁ TIỀM NĂNG LIÊN KẾT KHAI THÁC CÁC ĐIỂM DU LỊCH VÙNG PHỤ CẬN TỈNH LÂM ĐỒNG (2025)
Abstract: The regional linkage in tourism plays an important role in effectively exploiting the tourism resources, tourism products, tourism facility, etc. Being a big tourism center in Vietnam, Lam Dong has the potentials to connect with neighboring provinces to exploit the unique tourism routes attracting tourists. Therefore, evaluating the regional linkage in the vicinity not only meaningful to Lam Dong but also to neighboring provinces. Using the hierarchical analysis (AHP), this paper assesses 22 tourism sites in the vicinity of Lam Dong province. Results of the paper should be an important basis to give proposal, orientation for exploiting, making strategy in tourism development of Lam Dong province and its vicinity.